Pengaruh Self-Efficacy dan Kondisi Ekonomi Orang Tua terhadap Minat Melanjutkan Pendidikan Tinggi pada Siswa Kelas XII SMA Negeri 2 Woja Periode Akademik 2024/2025 (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to examine the influence of self-efficacy and parental economic conditions on the interest in pursuing higher education among 12th grade students at SMA Negeri 2 Woja during the 2024/2025 academic period. This study employs a quantitative approach using a closed-ended questionnaire distributed directly to respondents as the data collection method. The sample in this study was determined using purposive sampling techniques, resulting in a total of 96 respondents. Data analysis was conducted using the Partial Least Squares (PLS) approach with the assistance of SmartPLS version 4.0. The findings indicate that self-efficacy has a positive influence on students' interest in continuing higher education, and parental economic conditions have a positive influence on students' interest in continuing higher education. These findings are expected to contribute to policymakers and school authorities in developing appropriate approaches to encourage students' interest in continuing higher education, both through psychological reinforcement and socio-economic support.